Pengaruh Pemberian Konsentrasi Giberelin, Jenis Kemasan, Waktu Penyimpanan Terhadap Mutu Tomat - Breemer, Rachel; Pattiruhu, Gysberth (Universitas Pattimura, 2025)
Tomatoes have high economic and nutritional value but are highly perishable due to their high water content, necessitating appropriate handling strategies. These strategies include the use of inhibitors and specific packaging types. This study aimed to evaluate the effect of gibberellin treatment and storage systems on the chemical characteristics of tomatoes during storage. A factorial completely randomized design was employed with two factors. The results showed that the interaction between the inhibitor, packaging type, and storage duration had a significant effect on all parameters. The best treatment in this study was gibberellin at a concentration of 5 ppm combined with modified atmosphere packaging (MAP), which maintained the quality of tomatoes up to the 20th day of storage.